Low fT3/fT4 ratio as a proxy for muscle wasting in patients with advanced non-small cell lung cancer treated with pembrolizumab - Eccher, Serena; Sposito, Marco; Trestini, Ilaria; Scaglione, Ilaria Mariangela; Pasqualin, Luca; Tregnago, Daniela; Avancini, Alice; Insolda, Jessica; Confortini, Linda; Dodi, Alessandra; Stefani, Alessio; Cintoni, Marco; et al. (Frontiers in Oncology, 2025)
BackgroundLoss of skeletal muscle mass may serve as a valuable indicator of treatment efficacy and survival in individuals with lung cancer undergoing immunotherapy. This investigation sought to pinpoint accessible markers that could reflect the presence of muscle degradation.MethodsA retrospective study was conducted on patients with advanced non-small cell lung cancer (NSCLC) who received first-line pembrolizumab therapy from June 2018 to September 2021. Data collected included computed tomography (CT)-based body composition, clinical and radiological characteristics, along with thyroid function tests (free triiodothyronine [fT3] and free thyroxine [fT4]). Predictive factors were evaluated using multivariate logistic regression models.ResultsAmong 31 patients, muscle wasting was observed in 58.1%. Performance Status (PS) emerged as a strong predictor (p=0.005), and a significant link was also found between muscle depletion and fT3/fT4 ratio (p=0.0296). After adjusting for PS, the association with the hormone ratio remained suggestive though not statistically definitive (p=0.091). ROC curve analysis identified a threshold value of 2.84 for fT3/fT4 ratio, which best differentiated patients at higher versus lower risk of muscle loss. Notably, 77.3% of individuals with muscle wasting had a ratio below this cut-off, compared to only 14.3% of those with higher ratios (p=0.006). While no significant correlation was found between the hormone ratio and progression-free survival (PFS), a meaningful association with overall survival (OS) was observed (p=0.032).ConclusionsDespite the limited sample size, fT3/fT4 ratio appears to be a promising and accessible biomarker for identifying muscle wasting, which may be linked to diminished treatment response and shorter survival in patients with NSCLC.